EVALUATION OF ANTIBACTERIAL AND ANTIOXIDANT PROPERTIES OF LEAF EXTRACT OF CHRYSOPHYLLUM ALBIDUM AGAINST SELECTED ENTERIC BACTERIAL PATHOGENS - Odewade, Joseph O.; Odewade, L. O. (FUDMA JOURNAL OF SCIENCES, 2023)
This study investigated the antibacterial and antioxidant potentials of Chrysophyllum albidum leaf extract against selected enteric bacterial pathogens (Escherichia coli, Klebsiella pneumoniae, Shigella dysenteriae, Salmonella typhi, Proteus mirabilis and Proteus vulgaris). Fresh leaves of Chrysophyllum albidum were shade air-dried and ground into fine powder. Thereafter, the leaves powder was cold extracted using methanol and sterile distilled water in ratio 3:2(v/v). The mixture obtained was concentrated in vacuo using a rotary evaporator and lyophilized. The crude extract was screened for antibacterial, phytochemicals and antioxidant properties. The antibacterial properties were determined using agar well diffusion and agar dilution methods while the antioxidant and phytochemical assay were analyzed using standard methods. The phytochemical screening of the extract revealed the presence of tannins, alkaloids, flavonoids, saponins, steroids, terpenoids, reducing sugar and cardiac glycosides. The zones of inhibition shown by the extract at 10 mg/mL against the bacterial isolates ranged between 10 mm and 22 mm. The highest zone of inhibition (22 mm) was expressed against Escherichia coli at a concentration of 10 mg/mL. The MICs ranged between 1.25 mg/mL and 5mg/mL while MBCs ranged between 2.5 mg/mL and 10 mg/mL. The antioxidant assay of leaf extract showed appreciable antioxidant potential when compared with ascorbic acid used as standard. The leaf extract exhibited percentage of 92.03% at a concentration of 500 µg/mL while ascorbic acid exhibited percentage of 96.54% at the same concentration. This study, therefore showed that leaf extract of Chrysophyllum albidum exhibited significant antibacterial and antioxidant activities against the test isolates.